Effectiveness of the periodontal dressing upon periodontal parameters during treatment of gingival recession by free gingival graft - Karam, Bangen Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Various grafting procedures have been used to convert a thin periodontal phenotype to a thick phenotype, including free gingival graft. Objective: To evaluate the effectiveness of the periodontal dressing upon periodontal parameters such as Pocket depth, width of keratinized gingiva and recession depth during treatment of the Miller class I, II or III gingival recession of the lower anterior teeth. Materials and Methods: 34 lower anterior teeth with Miller class I, II or III gingival recession were selected and randomly grouped into two groups. The first group included 19 teeth and was treated with a single-step free gingival graft procedure with the application of the periodontal dressing. The second group had 15 teeth and was treated with a single-step free gingival graft (FGG) procedure without applying the periodontal dressing. Clinical parameters such as probing depth, the width of keratinized gingiva and recession depth were recorded before surgery (B0), two weeks (B1) and three months (B2) after surgery. Results: No significant differences (P0.05) in PD were observed in both groups at different time intervals and between both groups at two weeks and three months after surgery. However, a significant reduction (P0.05) in RD in both groups at two weeks and three months after the surgery was seen. Also, both groups saw a significant decrease (P0.05) at two weeks and three months after surgery. WKG was significantly (P0.05) increased at two weeks and three months after the surgery in both groups. The difference in the increase was highly significant (P0.001) between both groups at 2- weeks and 3-months after the surgery. Conclusions: The group that used periodontal dressing at 2-weeks and 3-months after surgery reported greater improvements in root coverage and increased width of keratinized gingiva compared to those who did not use periodontal dressing.
Keywords: Randomized controlled trial; gingival recession; free gingival grafts; periodontal dressing; gingiva